André Thevet, Pierre Belon and Americana in the Embroideries of Mary Queen of Scots. (18th December 2015) - Mason, Peter
The aim of this article is twofold: iconographic evidence is used to demonstrate the importance of the French connection (particularly André Thevet and Pierre Belon) for the sources of the American birds and animals in Mary Stuart's embroideries; and prosopographic evidence suggests that she and Thevet belonged to the same circle and may even have met at court during her youth in France.